Effects of Mesoscale Dynamics on the Path of Fast‐Sinking Particles to the Deep Ocean: A Modeling Study. Issue 7 (19th July 2022) - Wang, Lu; Gula, Jonathan; Collin, Jérémy; Mémery, Laurent
Abstract: The gravitational sinking of organic particles is a vital component of the biological carbon pump. This sinking process is strongly modulated by the spatiotemporally varying eddy field, complicating the interpretation of particle flux measured by deep‐moored sediment traps. By backtracking particles to 200 m depth based on the outputs of a realistic eddy‐resolving simulation, we characterize the origins of particles collected at a long‐term observatory site in the Northeast Atlantic and focus on the impact of mesoscale dynamics on particle transport. Our results show that mesoscale dynamics between 200 and 1, 000 m control the statistical funnel. Over the long term, the horizontal sampling scales of traps are estimated as hundreds of kilometers, with containment radius ranging from 90 to 490 km, depending on sinking velocities. Particle travel time suggests that overall vertical flow acts to facilitate the export, with estimated deviations up to 1 ± 2 days for particles sinking at 50 m d −1 to 1, 000 m. Statistical analyses of horizontal displacements reveal that mesoscale eddies at the site confine particle sources in a more local area. On average, particles in anticyclonic eddies sink faster to depth than expected from purely gravitational sinking, contrary to their counterparts in cyclonic eddies. The results highlight the critical role of mesoscale dynamics in determining particle transport in a typical open ocean region with moderate eddy kinetic energy. This study provides implications for the sampling design of particle flux measurements during cruises and the interpretation of deep‐ocean mooring observations. Plain Language Summary: As plants in the ocean, phytoplankton organisms transform the atmospheric CO2 into organic carbon that forms particles of various sizes sinking to the deep ocean due to gravity. The falling particles can be collected by containers called sediment traps. However, particles may originate far from the surface ocean directly above the trap as ocean currents horizontally transport particles. Also, the time taken by particles to sink to the deep ocean varies due to vertical motions of seawater. To study the impact of ocean currents on sinking particles, we use an ocean model and virtual particles. We release particles at a fixed location, representing a sediment trap, and track particle trajectories back in time to identify their source regions. Our results show that the size of this source region is mainly determined by currents between 200 and 1, 000 m. On average, particles tend to sink faster than expected from purely gravitational sinking. Large whirlpools of water above the trap lead to a local source region, which suggests that the particle flux can be better correlated to the surface production of organic carbon in this case. The finding has implications for the sampling strategy and the interpretation of particle export measurements in regional surveys. Key Points: The statistical funnel of deep‐ocean sediment traps is mainly determined by mesoscale dynamics in the twilight zone On average the vertical flow enhances particle sinking, but with more variance in spring than in other seasons Coherent eddies reduce the particle dispersion within a local area, with vertical acceleration (deceleration) by anticyclones (cyclones)